2016
DOI: 10.4103/1117-1936.196246
|View full text |Cite
|
Sign up to set email alerts
|

Cohort event monitoring of patients treated for uncomplicated malaria with artemisinin-based combination therapies in selected hospitals and community pharmacies in Nigeria

Abstract: Various types of AEs were seen and documented during the CEM programme. The findings suggested that the AA/AL monitored during this programme was generally safe and remarkably well tolerated among the Nigerian populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 1 publication
0
5
1
Order By: Relevance
“…but with a higher prevalence of anaemia (84.1%). It differed from the report by Bassi et al (2016) in Jos, who reported prevalence of anaemia in pregnant women to be 65.3% in first trimester. Similarly, Bankole et al (2012) in Benin city reported a higher prevalence of 78.9% malarial infection and 46.2% anaemia among the pregnant women.…”
Section: Discussioncontrasting
confidence: 93%
“…but with a higher prevalence of anaemia (84.1%). It differed from the report by Bassi et al (2016) in Jos, who reported prevalence of anaemia in pregnant women to be 65.3% in first trimester. Similarly, Bankole et al (2012) in Benin city reported a higher prevalence of 78.9% malarial infection and 46.2% anaemia among the pregnant women.…”
Section: Discussioncontrasting
confidence: 93%
“…This could be partly due to the perceived general safety of HMs (11) and unawareness of the inclusion of HMs among the products covered by PVG (unpublished data). Similarly, records have shown that most of the active surveillance of safety monitoring conducted in 2014 -2018 focused on antimalarial drugs (23,24). Thus, the NPC needs to improve on her activities such as (i) active surveillance of efficacy and safety of HMs, (ii) causality assessment of HMs-related reports, and (iii) awareness campaign and education of the public and relevant professionals on the need to report adverse reactions due to HMs.…”
Section: Discussionmentioning
confidence: 99%
“…In Nigeria, the National Pharmacovigilance Centre (NPC), a unit of the National Food and Drug Administration and Control (NAFDAC) is statutorily responsible for PVG activities (22). NPC has conducted several safety monitoring activities including cohort event monitoring of drugs (23), however, the efforts on HMs are considered inadequate. Similarly, few studies have evaluated the PVG system in Nigeria using the WHO indicators with a focus on conventional medicines (24).…”
Section: Introductionmentioning
confidence: 99%
“…The initial safety concerns observed by health care practitioners within the country with the introduction of the ACTs prompted the Federal Ministry of Health (FMOH) to carry out a pilot programme on Cohort Event Monitoring (CEM) across the six geopolitical zones of the country in 2009 (7). This was subsequently scaled up to a cohort of 10,000 patients in 2012 (8).…”
Section: Introductionmentioning
confidence: 99%